(untitled) (Research, Society and Development, 2023)
The present study proposed to systematically review case reports of metastasis to the oral cavity and compile epidemiological, clinical, radiological, and histopathological features, intending to identify common aspects that may favor early diagnosis of such condition. Articles were found by searching the following databases: PubMed; EMBASE; LIVIVO; Web of Science; LILACS; Scopus and SciELO. The search was carried out in March 2021 by two independent researchers, with no restrictions of publication date or language. A total of 2379 studies were retrieved and 60 articles completely matched inclusion criteria, totalizing 65 cases from 19 countries. Metastasis to oral cavity cases were slightly frequent in males (1.7:1) in the sixth decade of life, manifesting in oral soft tissues (58%, 37/65), mostly originated from the lungs (20%, 13/65) as primary site. Adenocarcinoma was the most reported type of malignacy. In 51% of cases the oral metastatic lesion was the first sign of cancer and 60% of the patients already presented metastasis to other locations. In 23% of the reports, only benign lesions were considered as diagnostic hypothesis, due to a remarkable clinical resemblance to hyperplastic, reactive lesions and odontogenic infections. The survival probability at 6 months after oral metastasis diagnosis was 49%. Metastatic lesions to the oral cavity are often misdiagnosed as benign lesions; due to its severity and quick progression, they must be considered in the differential diagnosis process, conducted by a multidisplinary healthcare team comprising an oral surgeon, especially for patients with history of cancer.